Scapular anatomy of Paranthropus boisei from Ileret, Kenya. Issue 125 (December 2018) - Green, David J.; Chirchir, Habiba; Mbua, Emma; Harris, John W.K.; Braun, David R.; Griffin, Nicole L.; Richmond, Brian G.
Abstract: KNM-ER 47000A is a new 1.52 Ma hominin scapular fossil belonging to an associated partial skeleton from the Koobi Fora Formation, Kenya (FwJj14E, Area 1A). This fossil effectively doubles the record of Early Pleistocene scapulae from East Africa, with KNM-WT 15000 (early African Homo erectus ) preserving the only other known scapula to date. KNM-ER 47000A consists of a complete glenoid cavity preserving a portion of the scapular spine and neck, the proximal half of the acromion, and a majority of the axillary border. A sufficient amount of anatomy is preserved to compare KNM-ER 47000A with scapulae of several Australopithecus species, extinct Homo, and living hominoids. The glenohumeral joint of KNM-ER 47000A is more laterally oriented than those of great apes and Australopithecus, aligning it closely with KNM-WT 15000 and modern humans. While this morphology does not imply a strong commitment to arboreality, its scapular spine is obliquely oriented—as in gorillas and some Australopithecus fossils—particularly when compared to the more horizontal orientation seen in KNM-WT 15000 and modern humans. Such a spine orientation suggests a narrow yet long infraspinous region, a feature that has been attributed to suspensory taxa. Accordingly, the morphology of KNM-ER 47000A presents conflicting behavioral implications. Nonetheless, a multivariate consideration of the available scapular traits aligns KNM-ER 47000A and Australopithecus with great apes, whereas KNM-WT 15000 resembles modern humans. The scapular morphology of KNM-ER 47000A is unique among fossil and extant hominoids and its morphological differences from KNM-WT 15000 strengthen the attribution of KNM-ER 47000 to Paranthropus boisei as opposed to early Homo . As the first evidence of scapular morphology in P. boisei, KNM-ER 47000A provides important new information on variation in hominin shoulder and upper limb anatomy from this critical period of hominin evolutionary history.